Transforming Triple Cropping System to Four Crops Pattern: An Approach of Enhancing System Productivity through Intensifying Land Use System in Bangladesh - Md. Aminul Islam; Md. Jahedul Islam; M. Akkas Ali; A. S. M. Mahbubur Rahman Khan; Md. Faruque Hossain; Md. Moniruzzaman (International Journal of Agronomy)
Changing three crops pattern to four crops can play a potential role for achieving countries food security. With this view to increase crop productivity, production efficiency, land use efficiency, and economic return through intensifying cropping intensity as well as crop diversity by transforming three crops pattern to four crops, the experiment was conducted in High Ganges River Floodplain Soils under the Agro-Ecological Zone (AEZ) 11 at Pali, Durgapur, under the Multilocation Testing Site, Puthia, Rajshahi, for two consecutive years 2014-15 and 2015-16. Four crops pattern mustard-onion/maize-T. Aman rice was tested at on-farm condition over the existing three crops pattern mustard-onion-T. Aman rice. Maize was introduced here as a relay crop with onion to fit it in the four crops pattern. The experiment was laid out in RCB design with six dispersed replications. Two-year crop cycles were completed, and data regarding component crops yield were considered for assessing the performance of the two cropping patterns for making a sense of comparing productivity. Although there was no significant difference in component crops yield between four crops and three crops pattern, as an additional crop, maize tremendously increased the system productivity and economic return of the four crops pattern. Higher rice equivalent yield 28.96 t·ha−1 in 2013-14 and 30.95 t·ha−1 in 2014-15 was recorded from the four crops pattern with a mean rice equivalent yield (REY) 29.95 t·ha−1 over the existing pattern with a mean value 21.76 t·ha−1. However, four crops pattern resulted in higher cultivation cost due to growing maize as an additional crop; nevertheless, it gave the higher gross return, marginal return, marginal benefit cost ratio, and production efficiency. The four crops pattern resulted averagely 37.63% higher production (REY) compared to the existing three crops pattern. Production as well as land use efficiency were increased by 9.33% and 19.18%, respectively, from the intensified alternate pattern.